Basal Ganglia : An Integrative View - Barrios, Fernando A.; Bauer, Clemens; Barrios, Fernando A.; Bauer, Clemens (IntechOpen, 2013)
The function of the Basal Ganglia is a subject of increasing prominence, not only among neuroanatomists, neurobiologists, cognitive-scientists and psychiatrists, but also among clinical ergonomists, rehabilitation, internal medicine and public health medics. This volume is the first of its kind. Scientists of diverse backgrounds join to explore issues about the Basal Ganglia from multiple angles. Basal Ganglia - An Integrative View explores the Basal Ganglia from diverse perspectives, sometimes as starting point others as end of diverse pathologies. It reaches from basic neuroanatomical explanations to higher-order integrative processes. It will be essential reading for both frontier neuroscientists and public health actors interested in the nature of Basal Ganglia and will offer a valuable example for the integration of leading research.
English
Keywords: Neurosciences; Neurosciences